Measurement of equivalent-circuit parameters for single-phase transformers with unknown turns-ratio and large series-branch impedances - Mukerji, , Saurabh Kumar; Singh, , Ghanshyam Kumar; Goel, , Sandeep Kumar; Basu, , Kartik Prasad (2006)
This paper describes a simple method for the determination of turns-ratio and equivalent-circuit parameters of single-phase transformers with large series-branch impedances. Based on test results, phasor diagrams are drawn which give formulas for the turns-ratio and equivalent circuit parameters with series-branch impedance split into low- and high- voltage components.